Intraobserver and Interobserver Agreement Among Obstetric Experts in Court Regarding the Review of Abnormal Fetal Heart Rate Tracings and Obstetrical Management. Issue 4 (December 2016) - Sabiani, L.; Le Dû, R.; Loundou, A.; d'Ercole, C.; Bretelle, F.; Boubli, L.; Carcopino, X.
Abstract : ( Am J Obstet Gynecol . 2015;213:856.e1–e.8) It has been noted that the fear of litigation has an impact on obstetricians and institutions, and obstetricians pay some of the highest premiums among physicians for malpractice insurance. The objective of this study was to evaluate the intraobserver and interobserver agreement among obstetric experts in court (OECs) regarding the retrospective review of abnormal fetal heart rate tracings (AFHRTs) and obstetrical management of patients with AFHRT during labor.